1996
DOI: 10.1097/00005537-199612000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Update: Laryngeal Reinnervation for Unilateral Vocal Cord Paralysis With the Ansa Cervicalis

Abstract: Eight patients underwent ansa cervicalis anastomosis to the adductor branch of the recurrent laryngeal nerve for unilateral vocal cord paralysis. They were followed long enough (at least 1 year) to determine if the procedure was successful. All cases have been subjected to preoperative and postoperative voice recording, acoustic analysis, and videolaryngoscopy. Some of them have been subjected to stroboscopy and electromyography (EMG). Data from these cases indicate that satisfactory phonatory quality may be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
54
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 15 publications
5
54
0
Order By: Relevance
“…Olsen et al reported excellent acoustic and perceptual results in a series of 12 patients. 15 In a series of 8 patiens, Zheng et al reported the return of mucosal waves after the procedure 16 and El-Kashlan et al had normal voices in each of three patients. 17 May and Beery had excellent results in a series of 20 patients undergoing the ansa-cercivalis reinnervation procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Olsen et al reported excellent acoustic and perceptual results in a series of 12 patients. 15 In a series of 8 patiens, Zheng et al reported the return of mucosal waves after the procedure 16 and El-Kashlan et al had normal voices in each of three patients. 17 May and Beery had excellent results in a series of 20 patients undergoing the ansa-cercivalis reinnervation procedure.…”
Section: Discussionmentioning
confidence: 99%
“…RLN reinnervation has several advantages over other techniques. It has the potential of restoring a normal or near-normal voice by returning thyroarytenoid muscle tone and bulk [6, 7, 9, 12, 13] in contrast with the conventional laryngoplasty procedure [7]. Reconstruction of the RLN in the management of UVFP during the thyroid cancer surgery is rarely reported [9, 1418].…”
Section: Discussionmentioning
confidence: 99%
“…With the development of microsurgical techniques, considerable success has been achieved in restoring the physiological function of denervated laryngeal muscles by laryngeal reinnervation, thereby enhancing phonation and optimizing vocal quality (Zheng et al 1996;Donghui et al 2010;Li et al 2013Li et al , 2014. However, the efficacy of delayed reinnervation remains unsatisfactory.…”
Section: Introductionmentioning
confidence: 99%